The Impact of Firm Size, Stock Liquidity, and Institutional Ownership on Stock Price Volatility: Evidence from State-Owned Enterprises Listed on the Indonesia Stock Exchange - Nabila Cahya Lestari; Inung Vias Dras Tistian Hening Tyas; Angelique Michella; Maufirotul Janna; Maria Yovita R Pandin (Journal of Economics, Assets, and Evaluation, 2025)
The purpose of this study is to examine the impact of institutional ownership, firm size, and stock liquidity on the stock fluctuations of state-owned enterprises (SOEs) in the Indonesian power sector, listed on the Indonesia Stock Exchange (IDX) during the period from 2022 to 2024. The dependent variable of this study is stock volatility, and the independent variables are firm size (log of total assets, market capitalization, total sales), stock liquidity (turnover rate, bid-ask spread, trading frequency, trading activity), and the ownership ratio of institutional investors (percentage of shares held by institutional investors, number of institutional investors, and ownership ratio of the largest institutional investor). This study employs a quantitative approach using the Partial Least Squares (SmartPLS) method. The results indicate that firm size has no significant effect on stock volatility, suggesting that the magnitude of corporate assets is not sufficient to significantly explain fluctuations in SOE stock prices. In contrast, stock liquidity has a significant effect on stock volatility, where high trading activity drives increased stock price fluctuations. In addition, institutional ownership also has a significant effect on stock volatility, indicating that the role of institutional investors can influence the dynamics of stock price movements. The low coefficient of determination indicates that SOE stock volatility is largely influenced by external factors outside the research model. This study is expected to serve as a consideration for investors and regulators in managing the risks of investing in SOE stocks.